Effect of Word of Mouth, Perception of Quality and Use oh Technology On Decisions of Application-Based Transportation Users (Study on Muslimah Community in Purwokerto) - Arini Hidayah; Fatmah Bagis; Mastur Mujib Ikhsani; Hermin Endratno (Jurnal Ilmiah Ekonomi Islam, 2021)
This study analyzes the effect of word of mouth, perceived quality, and use of technology on application-based transportation decisions. The method used in this research is a case study of the Muslim community in Purwokerto. Questionnaires were given to 100 respondents consisting of several members of the Muslim community in Purwokerto. The data analysis technique used is PLS (Partial Least Square) analysis using Smart PLS 3.0. The results showed that word of mouth had a significant positive effect on decisions to use application-based transportation, perceived quality had a significant positive effect on decisions to use application-based transportation, and use of technology had a negative effect on decisions to use application-based transportation.